Penerapan Model Pembelajaran Tipe Jigsaw Dalam Meningkatkan Hasil Belajar Ekonomi Perserta Didik Kelas XI IPS di SMAN-2 Palangkaraya - Sarinah Sarinah; Orhan Orhan (Neraca: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the increase in learning outcomes and learning activities of students in learning Economics. The type of this research is the Kolas Action Research (PTK) with the research subject of all students in the XI IPS 4 class of SMAN-2 Palangka Raya, which amounted to 34 students. The data collection technique in this study uses tests and observations. Data analysis uses qualitative and quantitative data analysis. The results of this study indicate that: (I) Economic learning activities through the use of the Jigsaw type cooperative learning model for students of class XI IPS 4 of SMAN 2 Palangka Raya active and well categorized. (2) the use of the Type Jigsaw Cooperative learning model dpalpal to improve student learning outcomes indicated by the acquisition of an average value of 66.32 in the first cycle increased to 80.20 in the IL cycle Classical learning completeness also increased with a value of 47% in the cycle I increased to 97% in the II cycle